On comparing side-channel properties of AES and ChaCha20 on microcontrollers - Najm, Zakaria (2019)
Side-channel attacks are a real threat to many secure systems. In this paper, we consider two ciphers used in the automotive industry - AES and ChaCha20 and we evaluate their resistance against side-channel attacks. In particular, the focus is laid upon the main non-linear component in these ciphers. Owing to the design of ChaCha20, it offers natural timing side-channel resistance and thus is suitable for affected applications. However, attacks exploiting the power side-channel are somewhat more difficult on ChaCha20 as compared to AES, but the overhead to protect ChaCha20 against such attack is considerably higher.